Evolução tectonotermal e processos multifásicos de mineralização de ouro no Depósito Turmalina, Quadrilátero Ferrífero, Brasil: geologia, análise estrutural, geotermometria e isópopos de enxofre - Wendell Fabricio da Silva (2016)
The Turmalina gold deposit is located in the NW of the world-class Quadrilátero Ferrífero iron-gold province, at the base of the Archean Rio das Velhas greenstone belt. The lithological succession consists of a volcano-sedimentary sequence intruded by the Mato Dentro Granitic Suite. The gold-bearing orebodies are confined to shear zones. The Archean G1 compressive event starts with an initial N-S shortening and then moves towards transport from the NNE to the SSW. The second generation of structures G2 is interpreted as the result of a continuous activity of the transpressional G1 shear zone however under ductile-brittle conditions. Three sulfides assemblages are identified, first two mineralized in gold. The first sulfide assemblage is associated with the G1 metamorphic peak that precedes the granitic intrusion at 2664±35 Ma. The second association of sulfides, remobilized during a decrease in temperature, is associated to the G2 event. Three generations of garnet were recognized. Grt1 depicts a pre- to syntectonic core and late-tectonic rim developed during the G1 event. Garnet-biotite temperatures yielded up to 625ºC for the cores and a minimum of 548°C for the rims. Grt2 is late- to post-tectonic, associated with the intrusion of the granite, yielding temperature near the peak of metamorphism. Grt3 occurs as late stage blasts overgrowing the pervasive G1-tectonic fabric. The 34S isotope values from the first and second sulfide assemblages range from 3.29 to 4.42 V-CDT and 2.94 to 5.76 V-CDT, respectively. In comparison with other gold deposits from worldwide, it is suggested that the Au derives from sedimentary and/or volcano-sedimentary layers such from the Nova Lima Group. The hydrothermal fluid responsible for the gold mineralization at the Turmalina deposit developed initially during prograde metamorphism at upper amphibolite facies conditions, shortly before the temperature peak associated with granitic intrusion, and continued until lower temperatures (around 510 oC). The gold remobilization and the formation of a second sulfide assemblage occurred at a post-metamorphic stage during the G2 event at temperatures between 490 and 366°C.